Effect of Sidoarjo Mud Inoculant and Bacillus subtilis on The Degradation of Tofu Liquid Waste in Microbial Fuel Cell Continuous Series Reactors - Juliastuti, Sri Rachmania; Pramoryza, Michellia; Darmawan, Raden (Journal of Fundamentals and Applications of Chemical Engineering, 2025)
The tofu industry in Indonesia generates large amounts of liquid waste with high BOD and COD, causing significant environmental impact. Microbial Fuel Cells (MFC) offer a sustainable solution for treating organic waste while generating electricity. Effective treatment of tofu liquid waste is essential. This study explores the use of Sidoarjo mud and Bacillus subtilis as inoculants in MFC systems, integrated with an advanced reactor design for improved degradation of pollutants. A Continuous Series Reactor was employed, equipped with an auto dosing pump for precise substrate feeding, optimizing microbial activity. The system was monitored using an Arduino Mega data logger and an ESP01 module for remote data transmission. The effectiveness of Sidoarjo mud and Bacillus subtilis was tested by measuring BOD, COD, and protein removal, with different inoculant combinations compared to a control group. The control group achieved BOD and COD removal rates of 70.43% and 47.92%, respectively. Sidoarjo mud alone improved these to 94.30% and 91.84%, while combining Sidoarjo mud with Bacillus subtilis increased removal rates to 94.70% and 92.55%. Protein degradation also improved by 79.79% with Bacillus subtilis. Sidoarjo mud and Bacillus subtilis effectively enhance waste degradation in MFC systems, providing a sustainable solution for tofu waste treatment.